Exercise muscle damage: the role of ACTN3 gene polymorphism - E. V. Orekhovskaya; A. V. Minin (Спортивная медицина: наука и практика)
Even the most experienced athletes are not safe from various types of muscle damage (cramp, contracture, sprain, tear and tear of the muscle). Nowadays, certain gene variations or polymorphisms associated with muscle damage caused by exercise are known. This review focuses on the polymorphism of the ACTN3 gene (Alpha-actinin-3 R577X, rs1815739), which plays an important role in the initial phase of muscle damage caused by exercises. Knowledge about how someone can respond to a specific type of exercises can help coaches individualize their athletes’ training exercises and thereby reduce the risk of injuries associated with overexertion. The purpose of this review is to provide a critical analysis of the literature on ACTN3 gene polymorphism associated with exercise-induced muscle damage both in young and old people, and the review highlights the potential mechanisms underlying these associations, which will provide a better understanding of exercise-induced muscle damage.